Out of the shadow of famine: evolving food markets and food policy in Bangladesh - Ahmed, Raisuddin; Haggblade, Steven; Chowdhury, Tawfiq-e-Elahi (International Food Policy Research Institute, 2000)
Over the past two decades, Bangladesh has transformed its food markets and food policies to free the country from the constant threat of famine. The authors, in this report, describe this remarkable transformation.